Alpha-lipoic acid, as an effective agent against toxic elements: a review - Vafaee, Farzad; Derakhshani, Mahla; Ghasemzadeh Rahbardar, Mahboobeh; Hosseinzadeh, Hossein (Naunyn-Schmiedeberg's archives of pharmacology, 2025)
This review aims to evaluate the efficacy of alpha-lipoic acid (ALA) in combating toxic elements, such as aluminum, arsenic, lead, mercury, and cadmium. The primary research question addressed is whether ALA can effectively mitigate the toxic effects of these metals through its antioxidant and chelating properties. Articles published between 1995 and 2024 were collected from Scopus, PubMed, Google Scholar, and Web of Science. Using Boolean (AND and OR), English-language publications were selected based on medical subject headings, titles, or abstracts that contained keywords related to ALA, metals, toxicity, antioxidants, and chelation. ALA supplementation significantly enhances cellular defense mechanisms and antioxidant enzyme activity. It effectively mitigates the adverse effects of aluminum exposure, counters arsenic toxicity in various cells and organs, and reduces cadmium toxicity, resulting in lower mortality rates among treated groups. Although ALA acts as a lead chelator, its efficacy is less than standard chelators. In the case of mercury, ALA shows beneficial effects in long-term therapy, although its capacity to reduce mercury concentration is limited. Overall, ALA emerges as a promising alternative for alleviating metal toxicity by enhancing antioxidant defenses, chelating toxic metals, and reversing their harmful effects. Further research in this area is encouraged to explore the full potential of ALA in mitigating the toxic effects of metals on biological systems.